PARTICIPATION OF PATIENTS AS AN ELEMENT OF SAFETY PROVISION — SPECIFIC FEATURES OF THE REMOTE FORMAT - Mintser, O. P.; Myronenko, N. V.; Sinienko, N. O.; Novyk А. М. (Medical Informatics and Engineering, 2020)
Background. The questions of introduction of the concept «4P» in practical medicine are considered. The problems of complex treatment of patients, participation and safety of patients are analyzed. Materials and methods. Results. The aim of the study is to substantiate the importance of the components of modern effective medicine: participation, communication, informatization, creation of multidisciplinary teams, as well as their changes in mobile medicine. Among the components of effective medicine, multidisciplinary approaches appear to be particularly relevant and important in the context of digital health services. It is emphasized that new regulatory acts are needed regarding the responsibilities of individual participants in the provision of medical care, especially in the case of remote (mobile) medicine, standards regarding the confidentiality and quality of patient survey and monitoring data. Conclusions. Multidisciplinary approaches affect both the overall decision-making process and all other key elements in the sequence of care delivery procedures — communication processes, the logic of participation, and, even, obtaining informed consent from the patient. It is also emphasized that ensuring continuity of care delivery, including the remote format, within a comprehensive (transmural) model of health care organization requires a unified scale of assessment of care delivery.